2003
DOI: 10.1038/sj.leu.2402860
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin induces apoptosis of B and T cells from B-cell chronic lymphocytic leukemia

Abstract: We have previously reported that prodigiosin (2-methyl-3-pentyl-6-methoxyprodigiosene) induces apoptosis in human hematopoietic cancer cell lines with no marked toxicity in nonmalignant cell lines. In this study, we demonstrate that prodigiosin induces apoptosis of B-cell chronic lymphocytic leukemia (B-CLL) cells (n ¼ 32 patients). The dose-response for the cytotoxic effect of prodigiosin was analyzed in cells from 12 patients showing an IC 50 of 116725 nM. Prodigiosin induced apoptosis of B-CLL cells through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 23 publications
1
61
0
1
Order By: Relevance
“…Additionally, prodigiosin induced apoptosis in Jurkat and HL-60 cells that were deficient in p53 (Vogelstein et al 2000). These results suggested that prodigiosin induced apoptosis independently of p53 and DNA damage (Campàs et al 2003). Also, prodigiosins promoted H+/Cl-, a symport activity leading to acidification of the cytosol.…”
Section: Drawbacksmentioning
confidence: 64%
See 3 more Smart Citations
“…Additionally, prodigiosin induced apoptosis in Jurkat and HL-60 cells that were deficient in p53 (Vogelstein et al 2000). These results suggested that prodigiosin induced apoptosis independently of p53 and DNA damage (Campàs et al 2003). Also, prodigiosins promoted H+/Cl-, a symport activity leading to acidification of the cytosol.…”
Section: Drawbacksmentioning
confidence: 64%
“…Other prodigiosins lack apoptotic activity, Prodigiosin is less toxic than fludarabine for normal T cells but exhibited similar effect in B-cell chronic lymphocytic leukemia (B-CLL) cells. Moreover, prodigiosin induced apoptosis in B-CLL cells that were resistant to treatment with fludarabine (Campàs et al 2003). Thus, these results suggested that inhibition of these signaling pathways could not explain the apoptotic activity of prodigiosins in B and T lymphocytes (Campàs et al 2003).…”
Section: Drawbacksmentioning
confidence: 73%
See 2 more Smart Citations
“…[9][10][11][12] There has also been considerable interest in natural products active against CLL cells, including the green tea polyphenol epigallocatechin-3-gallate 13 and the bacterial metabolite prodigiosin. 14 The sesquiterpene lactone parthenolide (PTL) has been widely used in traditional medicine for the treatment of migraines and inflammation. 15 This compound has recently been shown to induce apoptosis of hepatoma 16,17 and cholangiocarcinoma 18 cell lines and of primary acute and chronic myeloid leukemia cells 19 in vitro, with IC 50 values varying between 5 and 20 mM.…”
Section: Introductionmentioning
confidence: 99%